2022
DOI: 10.1039/d2an00717g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of multiple Alzheimer's disease biomarkers by SERS-LFA

Abstract: Alzheimer’s disease (AD) is one of the top public health crises in 21st century, especially in an aging society. Early diagnosis, prevention, and intervention can significantly reduce the risk of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…According to the Table 1, the sensor developed in our study exhibited higher enhancement and lower limit of detection (LoD) than the other reported sensors. This indicates that the fabricated sensor has the potential to accurately detect a biomarkers and their mixtures with good reproducibility and high selectivity [37–45] …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the Table 1, the sensor developed in our study exhibited higher enhancement and lower limit of detection (LoD) than the other reported sensors. This indicates that the fabricated sensor has the potential to accurately detect a biomarkers and their mixtures with good reproducibility and high selectivity [37–45] …”
Section: Resultsmentioning
confidence: 88%
“…This indicates that the fabricated sensor has the potential to accurately detect a biomarkers and their mixtures with good reproducibility and high selectivity. [37][38][39][40][41][42][43][44][45]…”
Section: Reproducibility and Recovery Timementioning
confidence: 99%
“…Then they are captured at the nanostructured T line, where the signal of SERS nanotags quantitatively detects them. Compared with previously reported SERS-LFIA, 19 the nanostructured SERS-LFIA enhances the sensitivity, offering great potential for the early non-invasive detection of AD biomarkers in blood. Human Ab 42 peptide, human Ab 40 peptide, human tau 441 protein, a pair of mouse anti-Ab 42 monoclonal antibodies, antitau monoclonal antibodies, and anti-Ab 40 monoclonal antibodies were provided by BioLegend, Inc. Human Neurofilament light chain (NFL) protein and a pair of mouse anti-human NFL antibodies were purchased from Abcam, Inc.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, SERS immunosensors have also been widely applied to other disease-associated proteins analysis. [18,[91][92][93][94][95][96][97] For example, Sun et al fabricated a SERS-microfluidic droplet platform based on the immune response occurring in water-in-oil droplets for simultaneous analysis of two angiogenic factors secreted by cancer cells. [98] In recent years, another kind of biological recognition element, aptamer has been widely applied to the SERS analysis of disease-related protein due to its advantages of good stability, easy modification, low price, no immunogenicity and so on.…”
Section: Proteinmentioning
confidence: 99%
“…These SERS‐based detection methods have offered a reliable and accurate new strategy for early diagnosis of liver cancer. Moreover, SERS immunosensors have also been widely applied to other disease‐associated proteins analysis [18,91–97] . For example, Sun et al.…”
Section: Label Sers Detectionmentioning
confidence: 99%